(untitled) (Strathmore Law Journal, 2025)
Plastic pollution is wreaking havoc in our societies, altering social, economic, cultural and environmental lives. The ubiquity of plastics and its low acquisition costs makes plastics permeate into every sector of our lives, a feature that presents difficulties in eradicating the crisis. From disrupting kinship systems to indigenous and local communities’ lifestyles, reversing plastic pollution requires a whole of society approach tapping into all knowledge types and systems that may provide the required solutions. This paper underscores the critical role of indigenous and local communities and their knowledge systems in combating plastic pollution. It argues that indigenous and local communities must be included in the discourses on addressing plastic pollution as they are custodians of valuable indigenous and traditional knowledge critical for combatting plastic pollution. Taking cue from the increasing recognition of the role of indigenous and traditional knowledge in environmental conservation, the paper argues that the integration of indigenous and traditional knowledge with emerging scientific methodologies provides profound insights in the search for pathways to a plastic-free planet.